Effectiveness of Boiled Sapodilla Leaves (Manilkara zapota) in Reducing the Number of Bacteria and Escherichia coli Germs on Eating Utensils - Agustina, Laili; Rahmawati, Rahmawati; Erminawati, Erminawati; Haris, Abdul (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Several studies have shown that the high number of germs in cutlery is due to the inability to carry out the sanitizing process. The sanitizing process can be done physically and chemically, using natural ingredients that contain active compounds such as flavonoids, tannins, and saponins, which function as antibacterials, such as sapodilla leaves. Sapodilla leaf boiled water can be a simple disinfectant for society to improve the quality of cutlery hygiene. The study aimed to determine the concentration of sapodilla leaf boiled water, which effectively reduces E. coli and the number of germs. The statistical test used was Kruskal Wallis, followed by a nonparametric post hoc test. A total of 24 swab samples were used with eight treatments and three repetitions. The results showed that the examination for the presence of E. coli on cutlery was negative. Examination of the germ count showed that the highest germ rate was in the control and the lowest was 10%. Statistical test results showed that a concentration of 10% is effective in reducing the germ number. This study concludes that E. coli in the samples were all negative, and the effective concentration in reducing the number of germs on cutlery is 10%, reducing from 60,768.11 colonies/cm2 to 12 colonies/cm2. Suggestions for future researchers are to conduct trials using other extraction methods.